Mechanistic Studies of Cu Electropolishing in Phosphoric Acid Electrolytes - Du, Bing; Suni, Ian Ivar (Journal of the Electrochemical Society, 2004)
Electropolishing of Cu and Cu/Ta/Si wafer samples were studied using a rotating disk electrode in a variety of phosphoric acid-based electrolytes, including several with ethanol and other species added as diluents. Diluents allow a wide range of water concentrations to be accessed and also reduce the dissolution rate during Cu electropolishing, simplifying possible applications to damascene processing. The measured limiting current densities are subject to a Levich analysis, demonstrating that water is the acceptor species involved in the rate-determining step. The effective diffusion coefficient that is determined is in almost exact agreement with that previously obtained from the electrohydrodynamic impedance, which does not require knowledge of the limiting species.